Verifying Defective PV-Modules by IR-Imaging and Controlling with Module Optimizers - Buerhop, Claudia; Fecher, Frank W.; Pickel, Tobias; Häring, Adrian; Adamski, Tim; Camus, Christian; Hauch, Jens; Brabec, Christoph (33rd European Photovoltaic Solar Energy Conference and Exhibition, 2017)
Quality control and efficient operation of roof-top, residential PV-installations is an economic and technical challenge because these PV-systems often suffer from various roof orientations and inclinations as well as partial and temporal shading. Module optimizers, which track the operating point individually for each module group, are good solutions providing also additional electrical information. The purpose of this work is verifying the identification and localization of defective PVmodules with IR-imaging and with module optimizers as well as quantifying the impact on the performance. Several PV-plants were inspected and carefully analyzed. The findings using IR-imaging can clearly be classified to substring failures due to open circuit and short circuit, bypass-diode faults, cell defect, and some undefined optimizer problems. The electric data reveal that these findings are related to certain power loss and monthly or annual yield reduction. Interesting is the temporal behavior of particular defective sites, which show short-term recovery. In summary, there is a good agreement between the occasionally performed IR-findings and the continuously monitored electrical data.
Keywords: Defects; Monitoring; Yield; IR Imaging; Thermography; Module Optimization/Optimisation